2012
DOI: 10.1111/j.1365-2028.2012.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in populations of elephant and other large herbivores in Gonarezhou National Park, Zimbabwe, as revealed by sample aerial surveys

Abstract: For 30 years, regular aerial surveys in Zimbabwean protected areas were funded, designed and executed primarily to estimate elephant numbers. Other large herbivores were recorded, even though some species were not easily seen from the air in savannah woodlands. Population estimates for species other than elephant provided indices of abundance that could be used to determine temporal trends in population size. This study tests for significant trends in the abundance of large herbivores in Gonarezhou National Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 26 publications
1
82
0
Order By: Relevance
“…4314/jasem.v18i1.18 Although precipitation may be the primary determinant of vegetation biomass in dry savanna ecosystems (Deshmukh 1984;Prins and Loth 1988;Sankaran et al 2005), in Gonarezhou National Park (hereafter, Gonarezhou), disturbances, such as herbivory, mainly from African elephant (Loxodonta africana) herbivory on baobabs (Adansonia digitata), droughts, fires and human activities may also likely influence baobab woodlands (Tafangenyasha 1997;Mpofu et al 2012;Kupika et al 2014). Between the year 1980 and 2012, elephant population in Gonarezhou increased from approximately 4700 to 9125 (Dunham 2012). Taken with the results of other aerial elephant surveys conducted post 1992 drought, elephants in Gonarezhou have increased at a mean annual rate of 6% during the past sixteen years.…”
mentioning
confidence: 59%
“…4314/jasem.v18i1.18 Although precipitation may be the primary determinant of vegetation biomass in dry savanna ecosystems (Deshmukh 1984;Prins and Loth 1988;Sankaran et al 2005), in Gonarezhou National Park (hereafter, Gonarezhou), disturbances, such as herbivory, mainly from African elephant (Loxodonta africana) herbivory on baobabs (Adansonia digitata), droughts, fires and human activities may also likely influence baobab woodlands (Tafangenyasha 1997;Mpofu et al 2012;Kupika et al 2014). Between the year 1980 and 2012, elephant population in Gonarezhou increased from approximately 4700 to 9125 (Dunham 2012). Taken with the results of other aerial elephant surveys conducted post 1992 drought, elephants in Gonarezhou have increased at a mean annual rate of 6% during the past sixteen years.…”
mentioning
confidence: 59%
“…Based on 2012 population estimates by Frederick (2013) combined with the MIKE data, we derive 5.17% elephant-carcass ratio in South Luangwa MIKE area. This maybe unsustainable as it exceeds the natural elephant population growth rate of 5% (Dunham, 2012;CITES et al, 2013). Based on the 2012 aerial survey results of the Lower Zambezi (Viljoen, 2013), the calculated elephant carcass ration is 2.68%.…”
Section: Discussionmentioning
confidence: 99%
“…Buffalo density in the northern part of KNP is higher than in the GNP (1·4 vs. 0·5 buffalo per km 2 ) [28,29]. In informal interviews, Pesvi farmers indicated that buffalo were regularly seen crossing from KNP into Zimbabwe.…”
Section: Unfenced Interfacementioning
confidence: 99%